Effects of Trichostatin A on Cumulus Expansion during Mouse Oocyte Maturation - Ming Du; Xiangwei Fu; Yanhua Zhou; Shien Zhu (Asian-Australasian Journal of Animal Sciences, 2013)
This study was conducted to investigate the effects of Trichostatin A (TSA) on cumulus expansion during mouse oocyte maturation. TSA treatment inhibited cumulus expansion and significantly reduced the cumulus expansion index (CEI) (p<0.05). To determine the underlying mechanism, the expression levels of several key factors that play crucial roles in cumulus expansion including components of extracellular matrix (ECM) (Has2, Ptgs2, Ptx3, and Tnfaip6) and Growth differentiation factor 9 (GDF9) were measured in control and TSA treated samples by real-time PCR. The effect of TSA on ERK phosphorylation (p-ERK1/2) in cumulus cells and GDF9 protein level in fully grown oocytes (FGOs) were detected by Western blotting. The expression levels of the ECM genes were significantly decreased (p<0.05) by TSA treatment while GDF9 expression did not response to TSA (p>0.05). TSA treatment blocked the activation of ERK1/2 (p<0.05) and had no significant effect on GDF9 protein expression (p>0.05). Collectively, these results suggested that TSA treatment altered ECM gene expression and blocked ERK1/2 activation to inhibit cumulus expansion in the mouse.